Formação de professores para a fluência tecnológico-pedagógica em tecnologia assistiva no curso de pedagogia - Lima, Edilma Machado de (2019)
Assistive Technology can break down barriers and provide disabled people with equality. For these people to be integrated, it is important that teachers are pedagogically, as well as technologically competent, since knowledge from these two processes go far beyond practice. Having this stated, it is extremely important for teachers to have studied and acquired knowledge in terms of Assistive Technology since initial formation. The aim of this research was to know how teacher training (TT) has been developed in the matter of Technological-Pedagogical Fluency (TPF) regarding Assistive Technology (AT) in the Pedagogy course of the State University of Rio Grande do Sul (UERGS). The principles of the cartographic method exposed in the Problem-Dialogical Matrix (PDM), Theme-Organizing Matrix (TOM), Theme- Analyzing Matrix (TAM) and also of the constructivist spiral planning, action, observation and reflection, typical from the participatory action research, have been used as guideline to the research with teachers and college students. The used resources for data collecting were the survey, participant observation, and documental analysis. This research used the principles of the social-historical educational theory, more specifically the postulates of Vigotsky. The results suggested that the university in study, UERGS, has been trying to suit university requirements, as well as modern needs drawn by public policies of special education and teacher training. However, most of these efforts depend on financial investments. Shortages in a more consolidated financing have been provoking losses in the quality of teacher training in the Pedagogy course. Concurrent to institutional issues, it is essential to invest in the enhancement of the TPF of the faculty in higher education so that teachers are capable of joining the AT when working in elementary education. The conclusion is that the development of TPF in teacher’s basic training is fundamental for the integration of the AT in a way it strengthens disabled people’s autonomy, social and cognitive competencies.